2017
DOI: 10.1371/journal.pntd.0005656
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin resistance in Aedes aegypti results in treatment failure in Merida, Mexico

Abstract: The operational impact of deltamethrin resistance on the efficacy of indoor insecticide applications to control Aedes aegypti was evaluated in Merida, Mexico. A randomized controlled trial quantified the efficacy of indoor residual spraying (IRS) against adult Ae. aegypti in houses treated with either deltamethrin (to which local Ae. aegypti expressed a high degree of resistance) or bendiocarb (to which local Ae. aegypti were fully susceptible) as compared to untreated control houses. All adult Ae. aegypti inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 35 publications
1
71
0
1
Order By: Relevance
“…aegypti [ 133 , 136 , 137 , 138 ]. Results to date are promising [ 117 , 139 , 140 , 141 ], but to be effective across the target species, IRS will require careful consideration of available insecticides because in both An. gambiae and Ae.…”
Section: Vector Surveillance and Control Of Aedes mentioning
confidence: 99%
“…aegypti [ 133 , 136 , 137 , 138 ]. Results to date are promising [ 117 , 139 , 140 , 141 ], but to be effective across the target species, IRS will require careful consideration of available insecticides because in both An. gambiae and Ae.…”
Section: Vector Surveillance and Control Of Aedes mentioning
confidence: 99%
“…Research in Merida, Mexico showed that treating inner house surfaces with bendiocarb has reduced Ae. aegypti infestation by 60% in three months period [20], and targeted IRS research in Cairns, Australia demonstrated that IRS along with location-based contact tracing had decreased the likelihood of dengue cases by 86% -96% in sprayed premises in comparison to unsprayed controls [21].…”
Section: Introductionmentioning
confidence: 99%
“…New formulations could last between five and eight months [70]. The potential evolution of insecticide resistance in the vector to pyrethroids can be controlled using alternative formulations, such as bendiocarb [75] and other new IRS formulations [67,73,76,77]. Good insecticide management is based on an alternation of formulations to combat the evolution of resistance, which may maintain efficacy over time, especially for location-specific interventions [70].…”
Section: Indoor Residual Spraying (Irs)mentioning
confidence: 99%